Lamb production in a mixture of italian ryegrass and white clover under different forage mass levels - Canto, Marcos Weber do; Moojen, Eduardo Londero; Carvalho, Paulo César de Faccio; Silva, José Henrique Souza da (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this research was to analyse the effects of different forage mass levels on lamb production. The experiment was conducted in Tupanciretã, Planalto Médio region at the State of Rio Grande do Sul, Brazil, in a mixture of italian ryegrass cv. Estanzuela 284 (Lolium multiflorum Lam.) + white clover cv. Yi (Trifolium repens L.), under different forage mass (FM) levels. The experimental design used was completely randommized, and the FM levels studied were: 1,119, 1,320, 1,477, 1,695, 2,146, 2,166, 2,410 and 2,483 kg/ha of dry matter (DM - kg/ha). The experimental period was from September 30 to December 8, 1992 and the animals used were cross lamb Ile de France x Corriedale early weaned (mean ± 80 days). Were evaluated the daily liveweight gain (DLG), gain per hectare (G/ha), stocking rate carryed, animals.day/ha and the DM of conversion efficience in kg of lamb liveweight. The results showed a positive linear relationship between DLG and G/ha with increased of FM levels. The FM levels higher to 2,400 kg of DM/ha reached 497 kg of total lamb liveweight gain/ha, and DLG/lamb of 0.12 kg/day. There was no FM levels effect at the stocking rate and animals.day/ha; there was a negative linear relationship between DM of conversion efficience with FM levels studied. The results show the effect of FM levels on animal response.